Much ado about nothing?- a comparative perspective on adult career guidance policies in Finland and Denmark - Pia Seidler Cort; Anne Larson; Samira Harjula; Mira Kalalahti; Kristina Mariager-Anderson; Minna Vilkman (Taylor & Francis Group, 2024)
Transnational organizations like the OECD and the EU have, for many years, focussed on adult career guidance (ACG) as a policy for solving problems, especially those related to the labour market and labour market transitions. In this article, we take a closer look into the development of ACG policies in Finland and Denmark. Drawing on multiple streams theory, we investigate how ACG policies have developed over time, identifying policy windows and the coupling of ACG policies as a solution to different policy problems. We compare across the cases of Finland and Denmark in order to identify similarities and differences with the aim of understanding the development of ACG policies considering the transnational call towards more coherent national systems. Methodologically, we use document analysis, including the examination of policy documents, legal documents, reports and research articles. The period studied spans from the 1990s until today, reflecting the developments at transnational level with the EU Commission and the OECD pushing for more coherent systems.